Learning in the natural environment to influence secondary school students' beliefs on the natural environment of Pulau Pangkor, Perak, Malaysia - Lim, Evelyn Ai Lin; Mariapan, Manohar (Forestry Department Peninsular Malaysia, 2019)
Learning about nature in its natural setting is a rare opportunity because schools are frequently inhibited by time and financial capabilities. The present study seeks to determine the influence of learning in the natural environment on secondary school students’ beliefs on Pulau Pangkor. Prior to the designing of the Student Research Assistant Programme, a focus group discussion was conducted with 10 secondary school students to elicit their thoughts and emotions towards the (a) natural environment of Pangkor, and (b) their involvement as students research assistants in the Pulau Pangkor Scientific Expedition. The findings of the focus group discussion were used to guide in the developing of the Student Research Assistant programme. Throughout the four-day programme, the students were attached to different research teams from various higher learning institutions and NGO. The Student Research Assistant programme provided a first-hand learning experience that was effective in influencing their beliefs towards the natural environment of Pangkor. The experiences also provided students a glimpse into the nature of the work of a field researcher and what research is all about besides contributing towards students’ personal development.